Differences in the Prevalence of Nocturnal Polyuria in the U.S. by Definition: Results from the Epidemiology of Nocturnal Polyuria Study. Issue 1 (21st July 2022) - Bosch, J. L. H. Ruud; Chapple, Christopher R.; Mueller, Elizabeth R.; Rosenberg, Matt T.; Chughtai, Bilal; Juul, Kristian; Coyne, Karin S.; Andersson, Fredrik L.; Bacci, Elizabeth D.; Simeone, Jason C.; Weiss, Jeffrey P.
Abstract : Purpose: Prevalence data on nocturnal polyuria (NP), nocturia caused by overproduction of urine during sleep, is primarily limited to men and varies by NP definition. This U.S.-representative epidemiological study of men and women ≥30 years old assessed the prevalence of NP. Materials and Methods: Consenting participants completed the baseline EpiNP (Epidemiology of Nocturnal Polyuria) survey (eg Lower Urinary Tract Symptoms Tool, comorbidities). All reporting ≥2 voids/night and a target of 100 random respondents reporting 0 or 1 void/night were asked to complete 3-day bladder diaries. NP was defined as nocturnal polyuria index (NPI) >0.33 (NPI33) and nocturnal urine production >90 ml/hour (NUP90). Extrapolated prevalence was stratified by sex and subgroups: idiopathic (without underlying causes), associated with overactive bladder (NPOAB), bladder outlet obstruction (NPBOO; men) and comorbidities. Voided volumes and timing, including first uninterrupted sleep period, were assessed by subgroup. Results: A total of 10, 190 individuals completed the baseline survey; mean age (range) was 54.4 (30–95). A total of 3, 938 individuals were invited to complete the diary; 1, 763 (49.3%) completed 3-day bladder diaries. Urine production (maximum nighttime volume, total volume, nocturnal urine production, nocturia index) was higher in both men and women with idiopathic NP and comorbidities. The median number of nighttime voids was greatest for NPBOO in men and NPOAB in women. Bother associated with nighttime voiding differed by NP subgroup but was highest in NPBOO for men (NPI33: 69.6%; NUP90: 71.1%) and NPOAB for women (NPI33: 67.5%; NUP90: 66.0%). Conclusions: This population-based NP prevalence study including men and women characterizes NP subgroups and provides insights into nocturia treatment by emphasizing factors influencing urine production versus factors influencing bladder capacity.